2021
DOI: 10.34172/ijtmgh.2022.05
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Camp and Patients in Arbaeen Pilgrimage in 2019

Abstract: Introduction: One of the largest religious gatherings in the world is the Arbaeen pilgrimage, which takes place on the 40th day after the anniversary of the martyrdom of Imam Hussein, the third Shiite Imam. This study was aimed to investigate how to set up the Sahib-al-Zaman treatment camp on the Arbaeen walking route in 2019 and the patients referring to it. Methods: This retrospective cross-sectional study was conducted on all patients referring to the Sahib-al-Zaman camp of Shiraz University of Medical Scie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Prior to making the Hajj, several vaccinations and vitamin boosters were recommended. Symptom‐based medications as prescribed were allowed with their proper use (Farahmand et al., 2022; Mushi et al., 2021). Health‐risk assessment and management, including technology‐based disease monitoring were included in the current trends regarding protecting their health status (Pane et al., 2019).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior to making the Hajj, several vaccinations and vitamin boosters were recommended. Symptom‐based medications as prescribed were allowed with their proper use (Farahmand et al., 2022; Mushi et al., 2021). Health‐risk assessment and management, including technology‐based disease monitoring were included in the current trends regarding protecting their health status (Pane et al., 2019).…”
Section: Resultsmentioning
confidence: 99%
“…A few studies reported the incidence of death as only 13.89% in this review. There was an incidence rate of about 44 deaths The most common communicable disease during the Islamic pilgrimage to Mecca was respiratory tract infection (Alasmari et al, 2020;Farahmand et al, 2022;Mushi et al, 2021). This was followed by several ambiguous infectious symptoms such as cough, fever, and sore throat.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation